Regional Cooperation and Economic Integration: Recent Evidence from ASEAN - Rama Vandika Daniswara; Ivana Ivana; Deshinta Rahma Dhani; Shafira Aulia Utami; Mohamad Dian Revindo (Universitas Negeri Malang, 2022)
The Asian financial crisis in 1997/98 and the global financial crisis in 2007/8 suggest that more research on economic integration is needed. This study aims to examine the depth and path of integration in the real and financial sectors among ASEAN member states during 1999-2019. The Augmented Dickey-Fuller–Generalised Least Squared (ADF-GLS) test results show stronger evidence of ASEAN real sector integration than its financial sector. Further, time lag analysis shows that the adjustments of interest rates in ASEAN countries are slower than those of price levels in the real economy. Academic and policy implications of the findings are provided, mainly on the need for stronger cooperation in ASEAN’s financial sector.